2023
DOI: 10.3389/feart.2022.1092409
|View full text |Cite
|
Sign up to set email alerts
|

Attribution analysis of runoff evolution in Kuye River Basin based on the time-varying budyko framework

Abstract: The underlying surface parameters in the Budyko framework (such as parameter n in the Choudhury–Yang equation) are crucial for studying the relationship between precipitation, evapotranspiration, and runoff. It is important to accurately quantify the influence of climate and human activities on the evolution of underlying surface characteristic parameters. However, due to the spatiotemporal heterogeneity of underlying surface parameters, it is often difficult to accurately quantify these relationships. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Liu et al [32] used the double cumulative curve method to identify the initial change year for streamflow and sediment transport in the KYH_W as 1979 and segmented the periods post-1980 into four intervals: 1950-1979, 1980-1996, 1997-2011, and 2012-2019, which were analyzed based on coal mining and vegetation cover data. Furthermore, Huang et al [34] utilized Pettitt's test to examine the change in streamflow in the KYH_W and pinpointed 1997 as the change year. Most studies on detecting change years in streamflow in the KYH_W exhibit significant consistency in the range of change points, predominantly falling between 1979 and 1980 and 1996 and 1999, with the stream-sediment relationship showing synchronicity with climate factors.…”
Section: Change Points In the Interannual Variations Of Watershed Run...mentioning
confidence: 99%
See 3 more Smart Citations
“…Liu et al [32] used the double cumulative curve method to identify the initial change year for streamflow and sediment transport in the KYH_W as 1979 and segmented the periods post-1980 into four intervals: 1950-1979, 1980-1996, 1997-2011, and 2012-2019, which were analyzed based on coal mining and vegetation cover data. Furthermore, Huang et al [34] utilized Pettitt's test to examine the change in streamflow in the KYH_W and pinpointed 1997 as the change year. Most studies on detecting change years in streamflow in the KYH_W exhibit significant consistency in the range of change points, predominantly falling between 1979 and 1980 and 1996 and 1999, with the stream-sediment relationship showing synchronicity with climate factors.…”
Section: Change Points In the Interannual Variations Of Watershed Run...mentioning
confidence: 99%
“…Research conducted in the middle reaches of the Yellow River has demonstrated that higher temperatures result in decreased basin runoff [43]. Huang et al [34] also found that temperature changes can alter watershed surface parameters, influencing runoff in addition to precipitation and potential evapotranspiration. Factors other than the Normalized Difference Vegetation Index (NDVI) contributed 24.96%, 22.36%, and 29.77% to runoff reduction in the KYH_W, WDHT_SW, and XM_SW, respectively, and 48.42%, 50.73%, and 41.43% to sediment yield reduction in the same sub-basins.…”
Section: Change Points In the Interannual Variations Of Watershed Run...mentioning
confidence: 99%
See 2 more Smart Citations
“…Affected by climate change and human activities, the spatial and temporal distribution of runoff in many river basins has changed significantly, disturbing the hydrological cycle and affecting the health of river ecosystems. Therefore, studying the main drivers of changes in runoff is key to global water forecasting and the basis for sustaining the sustainable use of freshwater resources [1 ].At this stage, the research and analysis of the causes of runoff changes in the river basin, from single to diverse influencing factors, has become one of the hot spots in the current hydrological research of the river basin.Huang et al [2] pointed out that frequent and complex human activities are the main reasons for the sharp decline of runoff in the loess high-atom basin. Xu et al [3] based on the study of runoff in the Weihe River Basin found that the drastic change of watershed characteristics caused by large-scale human activities is the main reason for the decrease of runoff in the watershed.…”
Section: Introductionmentioning
confidence: 99%